Efecto de la biofertilización en pasturas degradadas en la Cuenca del Salado - Rolon, Juan; Gargiulo, Alcira Maria; Otondo, Jose; Melani, Esteban; Andersen, Martin; Cicchino, Mariano Andres (Ministerio de Desarrollo Agrario de la Provincia de Buenos Aires, 2024)
Póster